1975
DOI: 10.1071/ar9750751
|View full text |Cite
|
Sign up to set email alerts
|

Congenital goitre in sheep in southern Tasmania

Abstract: Congenital goitre was first recorded in Tasmanian sheep In 1945. Severe but sporadic outbreaks have since occurred in 1956, 1964 and 1968. The disease seemed to be associated with particular farms and its incidence often differed markedly between ewe flocks on the one farm. A survey indicated that the condition was mainly confined to the Derwent Valley and the northern Midlands. Studies involved a grazing trial near Bothwell, where goitre was endemic, and included supporting animal house tnals and plant growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…Soil ingestion has been assumed to be an important factor in determining the iodine intake of grazing sheep since soil contains a higher iodine content than herbage (Healy et a1 1972). Sporadic outbreaks of goitre in lambs have been attributed to decreased soil ingestion by pregnant ewes grazing lush pastures (Statham and Bray 1975). Soil type, stocking rate, earthworm population, and management all effect the amount of soil ingested (Healy 1974).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil ingestion has been assumed to be an important factor in determining the iodine intake of grazing sheep since soil contains a higher iodine content than herbage (Healy et a1 1972). Sporadic outbreaks of goitre in lambs have been attributed to decreased soil ingestion by pregnant ewes grazing lush pastures (Statham and Bray 1975). Soil type, stocking rate, earthworm population, and management all effect the amount of soil ingested (Healy 1974).…”
Section: Discussionmentioning
confidence: 99%
“…Goitre and hypothyroidism due to iodine deficiency alone, or in combination with goitrogens, causes sporadic losses of newborn lambs in Tasmania (Statham and Bray 1975). New South Wales (Setchell er a1 1960), and Victoria (Caple et a f 1980).…”
Section: Introductionmentioning
confidence: 99%
“…1 DM (Statham & Bray 1975). Iodine has an important role in cell differentiation, and I demands of the foetus increase greatly during the last 4 weeks of gestation in sheep (Erenberg et al 1974).…”
Section: Discussionmentioning
confidence: 99%
“…There have been several reports of outbreaks of goitre in domestic animals in Tasmania (Southcott 1945;Green 1956;Clements 1957). More recently Statham and Bray (1975) and one of us (R.W.M.) have found that ovine congenital goitre is regionally distributed.…”
Section: Discussionmentioning
confidence: 96%